Homeostatic action of adenosine A3 and A1 receptor agonists on proliferation of hematopoietic precursor cells - Hofer, Michal; Pospíšil, Milan; Znojil, Vladimír; Holá, Jiřina; Štreitová, Denisa; Vacek, Antonín (Experimental biology and medicine, 2008)
Two adenosine receptor agonists, N6-(3-iodobenzyl)adenosine-5'-N-methyluronamide (IB-MECA) and N6-cyclopentyladenosine (CPA), which selectively activate adenosine A3 and A1 receptors, respectively, were tested for their ability to influence proliferation of granulocytic and erythroid cells in femoral bone marrow of mice using morphological criteria. Agonists were given intraperitoneally to mice in repeated isomolar doses of 200 nmol/kg. Three variants of experiments were performed to investigate the action of the agonists under normal resting state of mice and in phases of cell depletion and subsequent regeneration after treatment with the cytotoxic drug 5-fluorouracil. In the case of granulopoiesis, IB-MECA 1) increased by a moderate but significant level proliferation of cells under normal resting state; 2) strongly increased proliferation of cells in the cell depletion phase; but 3) did not influence cell proliferation in the regeneration phase. CPA did not influence cell proliferation under normal resting state and in the cell depletion phase, but strongly suppressed the overshooting cell proliferation in the regeneration phase. The stimulatory effect of IB-MECA on cell proliferation of erythroid cells was observed only when this agonist was administered during the cell depletion phase. CPA did not modulate erythroid proliferation in any of the functional states investigated, probably due to the lower demand for cell production as compared with granulopoiesis. The results indicate opposite effects of the two adenosine receptor agonists on proliferation of hematopoietic cells and suggest the plasticity and homeostatic role of the adenosine receptor expression.
Keywords: buňky kostní dřeně; agonisté adenosinového receptoru A3; Receptor, Adenosine A1; Cell Proliferation; hematopoetické kmenové buňky; granulocyty; Mice; zvířata; agonisté adenosinového receptoru A1; adenosin; Adenosine A1 Receptor Agonists; Financing, Organized; Homeostasis; financování organizované; Adenosine A3 Receptor Agonists; Neurotransmitter Agents; mužské pohlaví; Receptor, Adenosine A3; proliferace buněk; receptor adenosinový A3; Granulocytes; myši inbrední CBA; Mice, Inbred CBA; neurotransmiterové látky; receptor adenosinový A1; myši; Dose-Response Relationship, Drug; Hematopoietic Stem Cells; Animals; vztah mezi dávkou a účinkem léčiva; Erythroid Cells; Mice, Inbred C57BL; erytroidní buňky; Adenosine; Male; homeostáza; Bone Marrow Cells; myši inbrední C57BL